2019
DOI: 10.37190/abb-01457-2019-01
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral dentoalveolar asymmetries in female patients with adolescent idiopathic scoliosis

Abstract: The aim of this cross-sectional research was to quantify left-right dentoalveolar fluctuating (FA) and directional asymmetries (DA) in patients with adolescent idiopathic scoliosis and to assess the relationship between these asymmetries and the side, location, and severity of scoliosis. Materials and methods: The study group comprised of 60 females aged 12-16 years, with idiopathic scoliosis, and 54 healthy controls. Measurements were made with the use of digital caliper on full-mouth dental casts. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This proportion between both types of asymmetry is clearly lower than the one observed in other studies, in which the amount of FA is subtle when compared to the DA effect (Balzeau et al, 2011;Benítez et al, 2020;Valen, 1962). However, in a recent study of FA of the bilateral dentoalveolar asymmetries in patients with AIS, a greater presence of significant FA effect on the bilateral trait has been detected in patients rather than in controls (Lewandowska et al, 2019). This result, which *p-value < 0.05 is statistically significant.…”
Section: About the Resultsmentioning
confidence: 86%
“…This proportion between both types of asymmetry is clearly lower than the one observed in other studies, in which the amount of FA is subtle when compared to the DA effect (Balzeau et al, 2011;Benítez et al, 2020;Valen, 1962). However, in a recent study of FA of the bilateral dentoalveolar asymmetries in patients with AIS, a greater presence of significant FA effect on the bilateral trait has been detected in patients rather than in controls (Lewandowska et al, 2019). This result, which *p-value < 0.05 is statistically significant.…”
Section: About the Resultsmentioning
confidence: 86%
“…A total of 14 studies ( 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ) met the eligibility criteria and were included in the review ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although bilateral asymmetries are accepted to be a common feature of occlusions, 16 , 17 , 21 opinions about the etiology of occlusal asymmetries differ. A cross-sectional study by Lewandowska et al 16 confirmed bilateral dentoalveolar asymmetries in patients with adolescent IS. However, another IS study 17 reported a functional lateral mandibular displacement in two individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recent research on this topic involved cross-sectional studies that focused on the morphological and functional abnormalities of the stomatognathic system in patients with IS. 16 , 17 However, the dental-occlusal features in patients with congenital scoliosis (CS) have been rarely reported. Therefore, in the present study, we included cases of IS and CS and hypothesized that IS and CS patients have different patterns of malocclusions in comparison with healthy children.…”
Section: Introductionmentioning
confidence: 99%